The Educational Ideas of KH. Muhammad ‎Syamsul Arifin and Their Relevance to Modern ‎Education: From 1980 to 2021‎ - Abdul Mukit (State Islamic Institute of Madura, 2023)
The objective of this research is to uncover the educational ideas presented by Kiai Muhammad and their consistent application in LPI Darul Ulum Pondok Banyuanyar Pesantren Pamekasan, which is one of Indonesia's oldest Pesantrens, from the year 1980 to 2021. Additionally, the aim is to explore the significance of these ideas in the context of contemporary education. This study involves qualitative research using library and content analysis as an analysis technique to examine both primary and secondary data sources. The Primary data sources come from the written works of Kiai Muhammad, namely the book